The Influence of Fear of Missing Out (FoMO), Influencer Marketing, and Viral Marketing on Pop Mart's Blind Box Purchase Intention - Setiawati, Lora; Yusuf, Yusuf (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The increasing use of social media along with the development of the concept  of the experience economy has encouraged changes in the consumption patterns of the younger generation, especially for hedonic products that emphasize elements of experience, such as blind boxes. Pop Mart as a global blind box brand shows rapid growth in Indonesia, which is triggered by the rise of unboxing content, the role of influencers, and the implementation of viral marketing strategies  that have given rise to the FoMO phenomenon. This study is aimed at examining the influence of FoMO, Influencer Marketing, and Viral Marketing on Pop Mart blind box product Purchase Intention. This study was carried out through a quantitative approach using the PLS-SEM method to 200 respondents in Cirebon City who actively use social media and have seen blind box content. The results show that FoMO, Influencer Marketing, and Viral Marketing produce a positive and significant influence on Purchase Intent, either separately or simultaneously. Among the three variables, FoMO had the most dominant influence, and the research model was able to explain 63.8% of the variation  in Purchase Intention. These findings confirm the important role of consumer psychological factors and digital marketing strategies in shaping the purchase intention of blind box products.